1992
DOI: 10.1017/s0043174500057039
|View full text |Cite
|
Sign up to set email alerts
|

Fluroxypyr Absorption and Translocation in Leafy Spurge (Euphorbia esula)

Abstract: Absorption and translocation of14C-fluroxypyr were determined for leafy spurge at various growth stages, under differing relative humidity and temperature conditions, and when applied with picloram or 2,4-D. Absorption of14C-fluroxypyr was greater in vegetative plants (39%) than in flowering or postflowering plants (25%), while total translocated to roots averaged 2% of applied herbicide regardless of growth stage. Greater14C-fluroxypyr absorption and translocation occurred in plants exposed to high relative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Forty percent of applied [i4C]-AC 263,222 was absorbed into the plant 2 OAT with no significant increase in absorption through 8 OAT (Table 1). AC 263,222 absorption by leafy spurge was greater than that reported for picloram (14%) (Lym and Moxness 1989;Moxness and Lym 1989;Thompson et al 1996) and quinclorac (0% without lutensol) (Lamoureux and Rusness 1995), similar to that reported for 2,4-0 (34 to 78%) (Lym and Moxness 1989;Thompson et al 1996) and fluroxypyr (48%) (Lym 1992) absorption, but less than that reported for imazapyr (80%) (Nissen et al 1995) and glyphosate (81 %) (Maxwell et al 1987). Imazethapyr absorption by leafy spurge ranged from 20 to 80% and was dependent on the use adjuvants, especially VAN and ammonium sulfate (AS) (Thompson et al 1996).…”
Section: Absorption Translocation and Root Releasesupporting
confidence: 81%
“…Forty percent of applied [i4C]-AC 263,222 was absorbed into the plant 2 OAT with no significant increase in absorption through 8 OAT (Table 1). AC 263,222 absorption by leafy spurge was greater than that reported for picloram (14%) (Lym and Moxness 1989;Moxness and Lym 1989;Thompson et al 1996) and quinclorac (0% without lutensol) (Lamoureux and Rusness 1995), similar to that reported for 2,4-0 (34 to 78%) (Lym and Moxness 1989;Thompson et al 1996) and fluroxypyr (48%) (Lym 1992) absorption, but less than that reported for imazapyr (80%) (Nissen et al 1995) and glyphosate (81 %) (Maxwell et al 1987). Imazethapyr absorption by leafy spurge ranged from 20 to 80% and was dependent on the use adjuvants, especially VAN and ammonium sulfate (AS) (Thompson et al 1996).…”
Section: Absorption Translocation and Root Releasesupporting
confidence: 81%
“…Absorption of 14 C-quinclorac averaged 79% within 48 HAT in leafy spurge (Lamoureux and Rusness 1995). However, picloram absorption was less than 30% in several studies (Lym and Messersmith 1990;Lym and Moxness 1989), while fluroxypyr absorption ranged from 39% when leafy spurge was in the vegetative stage to 24% in the postflower stage (Lym 1992b). A maximum of 40% of imazapic was absorbed in leafy spurge within 48 HAT (Thompson et al 1998).…”
Section: Resultsmentioning
confidence: 94%
“…Relative humidity directly affects the hydration and wax density of the leaf cuticle; thus, absorption and translocation of foliar-applied herbicides is typically greater under conditions of high RH (Muzik 1976;Richardson 1977). For example, Lym (1992) reported an increase in absorption and translocation of 14 C-fluroxypyr applied to leafy spurge (Euphorbia esula L.) when plants were exposed to 90% RH compared with 30% RH. However, the physiochemical properties of the leaf differ among plant species (Holloway 1970), which might explain why kochia did not respond to fluroxypyr the same as Palmer amaranth when plants were grown under controlled conditions.…”
Section: Resultsmentioning
confidence: 99%